Public Bureaucracy from the Perspective of the State Budget - Markova, Hana (Public Governance, Administration and Finances Law Review, 2019)
The state covers needs that are necessary for the running of the state from its revenues (most often from tax revenues). If territorial self-governments exist, certain public goods are funded from territorial budgets. The state contributes concurrently to territorial self-governing units to the performance of delegated powers – most often through subsidies. The contribution to the performance of state administration can be considered one of these subsidies. At all levels of government, the effect of bureaucracy is manifested in the form of coercion consisting of the use of “normative” power and “rewarding” power.